Clinical characteristic and outcome of lymphoplasmacytic lymphoma of non‐Waldenstrom macroglobulinemia type: A Swedish lymphoma registry study. (27th December 2021) - Brandefors, Lena; Sander, Birgitta; Lundqvist, Kristina; Kimby, Eva
Summary: Lymphoplasmacytic lymphoma (LPL) not fulfilling the WHO diagnostic criteria (2017) for Waldenstrom's macroglobulinemia (WM) (named non‐WM LPL) is a rare disease and only a few systematic studies have been published. Here, we present a population‐based study of non‐WM LPL focusing on diagnostic difficulties, patient characteristics, and outcome. From 1511 patients included in the Swedish Lymphoma Registry 1 Jan 2000 – 31 Dec 2014 with a diagnosis of WM/LPL, we could confirm the diagnosis of non‐WM LP in only 33 patients. The median age at diagnosis was 69 years. A paraprotein was found in most (IgG in 54%, IgA in 15%) and 12% of the cases were non‐secretory. Compared with the WM patients, the non‐WM LPL patients were younger, had more adverse prognostic factors such as elevated LDH, anaemia, and lymphocytosis at diagnosis. In addition, the non‐WM LPL patients more often were symptomatic and received treatment at diagnosis. The overall survival (OS) did not significantly differ between the non‐WM LPL and WM groups (P = 0.247), with a median survival time of 71 and 96 months, respectively. To conclude, we found differences in clinical features between WM and non‐WM LPL, but no difference in survival.